MiR-33a targets FOSL1 and EN2 as a clinical prognostic marker for sarcopenia by glioma - Wang, Wei; Liu, Wei; Xu, Jing; Jin, Hongze (Frontiers in Genetics, 2022)
In order to determine the relationship between glioma and muscle aging and to predict prognosis by screening for co-expressed genes, this study examined the relationship between glioma and sarcopenia. Eight co-downregulated miRNAs, three co-upregulated miRNAs, as well as seven genes associated with overall glioma survival, were identified, including KRAS, IFNB1, ALCAM, ERBB2, STAT3, FOSL1 and EN2. With a multi-factor cox regression model incorporating FOSL1 and EN2, we obtained ROC curves of 0.702 and 0.709, respectively, suggesting that Glioma prognosis can be predicted by FOSL1 and EN2, which are differentially expressed in both cancer and aged muscle. FOSL1 and EN2 were analyzed using GSEA to identify possible functional pathways. RT-qPCR and a dual-luciferase reporter gene system verified that has-miR-33a targets FOSL1 and EN2. We found that has-mir-33a co-targeting FOSL1 and EN2 has good predictive value for glioblastoma and skeletal muscle reduction.